INFECTION PREVENTION AND CONTROL - KEY TO SUCCESS IN CONTAINING COVID-19 - Mirza, Irfan Ali; Zafar, Humaira; Hussain, Wajid; Jaffar, Syed Raza (Pakistan Armed Forces Medical Journal, 2020)
In the current pandemic of corona viralinfection disease, 2019 (COVID-19), the acquiescence for infection prevention and control is necessary at all levels. Therefore,this commentary was written with an objective to identify the evidence for infection prevention and control in orderto contain COVID-19. In order to minimize the spread of COVID-19, there comes a dire need for taking all necessary measures at community and health care level. From community perspective and for general public awareness to adopt social distancing protocols, involvement of social medias can be helpful. While necessary measures are recommended to be taken in health care setting, for the safetyof both the health care professionals (HCPs) and patients. Published evidence had emphasized mandatory wearing of personal protective equipments (PPEs). Amongst all PPEs, the focus for HCPs was to wear N95 mask, gloves, gowns, face shield and goggles. Theuse of good quality ofpersonal protective equipment(PPEs)was emphasized. For patient’ssafety wearing of gloves and masks was also accentuated. Proper disinfection ofhealth care settings is recommended to prevent the spread of infection. Itis concluded that use of various infection prevention and control measures at community and health care settings are themandatory steps to control the spread of COVID-19.